NATURALNESS OF RACISM IN SENSATIONALIST PRESS - Lino Salvador, Luis (2008)
This article analyses racist discourse and practices in sensacionalist press through thereview of some popular dailies in order to demonstrate internalization of racist viewsby the readers who see them as normal, as they come camouflagcd by ludicrous amlironic discourse.